2007
DOI: 10.1111/j.1600-0536.2006.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl esterification of 15‐hydroperoxyabietic acid does not affect the patch‐test result in colophonium allergic patients

Abstract: Colophonium (gum rosin) consists of numerous compounds. We have previously shown that abietic acid (Fig. 1), the major compound in gum rosin, is oxidized to strong contact allergens at air exposure (1). The most potent allergen identified is 15-hydroperoxyabietic acid (15-HPA, Fig. 1), which was isolated as its methyl ester (Fig. 1) and used for patch testing (2, 3). The aim of this study was to confirm the previous postulate that methyl esterification of the carboxyl group in 15-HPA does not affect the allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A variety of other oxidation products from abietic acid and dehydroabietic acid (the other major resin acid in colophony) were isolated and identified, some of which were shown to be sensitizers in guinea pig studies . Clinical investigations have shown that patch testing with 29 detects about 50% of the patients with contact allergy to colophony , .…”
Section: Activation Of Nonsensitizing Compounds By Air Oxidationmentioning
confidence: 99%
“…A variety of other oxidation products from abietic acid and dehydroabietic acid (the other major resin acid in colophony) were isolated and identified, some of which were shown to be sensitizers in guinea pig studies . Clinical investigations have shown that patch testing with 29 detects about 50% of the patients with contact allergy to colophony , .…”
Section: Activation Of Nonsensitizing Compounds By Air Oxidationmentioning
confidence: 99%
“…Colophonium (rosin) is a natural resin derived from pine. It contains numerous chemical compounds, mostly abietic acid and its derivatives …”
mentioning
confidence: 99%